Reaction Mechanisms in Carbon Dioxide Conversion - Aresta, Michele; Dibenedetto, Angela; Quaranta, Eugenio (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book provides an analysis of the reaction mechanisms relevant to a number of processes in which CO2 is converted into valuable products. Several different processes are considered that convert CO2 either in specialty chemicals or in bulk products or fuels. For each reaction, the mechanism is discussed and the assessed steps besides the dark sites of the reaction pathway are highlighted. From the insertion of CO2 into E-X bonds to the reduction of CO2 to CO or other C1 molecules or else to C2 or Cn molecules, the reactions are analysed in order to highlight the known and obscure reaction steps. Besides well known reaction mechanisms and energy profiles, several lesser known situations are discussed. Advancing knowledge of the latter would help to develop efficient routes for the conversion of CO2 into valuable products useful either in the chemical or in the energy industry. The content of this book is quite different from other books reporting the use of CO2. On account of its clear presentation, "Reaction Mechanisms in Carbon Dioxide Conversion" targets in particular researchers, teachers and PhD students.